Regulación jurídico penal del transfemicidio en ecuador: un reconocimiento a los derechos de la comunidad transgénero - Ortiz Caiza, Vivian Nahobi (2025)
The need to understand the legal consequences of the murder of transgender women due to their female gender has led to the development of this research paper. Its objective was to analyse the inclusion of transfemicide in Ecuadorian criminal legislation as a guarantee of the rights of the transgender community. A document analysis methodology was used, reviewing legal doctrine, jurisprudence, and Ecuadorian criminal law as well as comparative law. The main findings highlighted that violent crimes against the LGBTQ+ community in Ecuador were committed with greater cruelty against transgender women. Although there are policies to protect LGBTQ+ rights, their implementation is insufficient. Currently, the promotion of the transfemicide category in Ecuador is underway. The Ecuadorian Comprehensive Organic Criminal Code (COCC) provides an unclear definition of the legal term gender identity, which is referenced in Article 11, Paragraph 2 of the Constitution. The data obtained through this research revealed that Ecuadorian legislation does not guarantee the rights of the transgender community and fails to provide legal equality and inclusion for transgender individuals. Ecuadorian legislation must focus on protection against discrimination, hate crimes, and gender-based protections. It was concluded that legal science limits the protection afforded to transgender women. Therefore, it is necessary to discuss the inclusion of transfemicide to effectively punish the murder of transgender women from an adequate gender perspective, thereby ensuring an effective justice system.